Conservation planning on China's borders with Myanmar, Laos, and Vietnam - Wang, Lin; Yang, Bin; Bai, Yang; Lu, Xiaoqiang; Corlett, Richard T.; Tan, Yunhong; Chen, Xiao‐Yong; Zhu, Jianguo; Liu, Yan; Quan, Rui‐Chang (Conservation biology, 2021)
Transboundary conservation is playing an increasingly important role in maintaining ecosystem integrity and halting biodiversity loss caused by anthropogenic activities. However, lack of information on species distributions in transboundary regions and understanding of the threats in these areas impairs conservation. We developed a spatial conservation plan for the transboundary areas between Yunnan province, southwestern China, and neighboring Myanmar, Laos, and Vietnam in the Indo‐Burma biodiversity hotspot. To identify priority areas for conservation and restoration, we determined species distribution patterns and recent land‐use changes and examined the spatiotemporal dynamics of the connected natural forest, which supports most species. We assessed connectivity with equivalent connected area (ECA), which is the amount of reachable habitat for a species. An ECA incorporates the presence of habitat in a patch and the amount of habitat in other patches within dispersal distance. We analyzed 197,845 locality records from specimen collections and monographs for 21,004 plant and vertebrate species. The region of Yunnan immediately adjacent to the international borders had the highest species richness, with 61% of recorded species and 56% of threatened vertebrates, which suggests high conservation value. Satellite imagery showed the area of natural forest in the border zone declined by 5.2% (13,255 km2) from 1995 to 2018 and monoculture plantations increased 92.4%, shrubland 10.1%, and other cropland 6.2%. The resulting decline in connected natural forest reduced the amount of habitat, especially for forest specialists with limited dispersal abilities. The most severe decline in connectivity was along the Sino‐Vietnamese border. Many priority areas straddle international boundaries, indicating demand and potential for establishing transboundary protected areas. Our results illustrate the importance of bi‐ and multilateral cooperation to protect biodiversity in this region and provide guidance for future conservation planning and practice. Planeación de la Conservación en las Fronteras de China con Myanmar, Laos y Vietnam Resumen La conservación transfronteriza cada vez juega un papel más importante en la preservación de la integridad del ecosistema y en el freno a la pérdida local de la biodiversidad causada por las actividades antropogénicas. Sin embargo, la falta de información sobre la distribución de las especies en las regiones transfronterizas y de la comprensión de las amenazas en estas áreas obstaculiza la conservación. Desarrollamos un plan de conservación espacial para las áreas transfronterizas entre la provincia de Yunnan, al suroeste de China, y los países vecinos Myanmar, Laos y Vietnam localizadas en el punto caliente de biodiversidad Indo‐Burma. Para identificar las áreas prioritarias para la conservación y la restauración, determinamos los patrones de distribución de las especies y los recientes cambios en el uso de suelo y examinamos las dinámicas espaciotemporales del bosque natural conectado, el cual mantiene a la mayoría de las especies. Evaluamos la conectividad con el área equivalente conectada (AEC), que es la cantidad de hábitat accesible para una especie. Un AEC incorpora la presencia del hábitat en un fragmento y la cantidad de hábitat en otros fragmentos dentro de la distancia de dispersión. Analizamos 197,845 registros de localidades desde colecciones de especímenes y monografías para 21,004 especies de plantas y de vertebrados. La región de Yunnan inmediatamente adyacente a las fronteras internacionales tuvo la riqueza de especies más alta con el 61% de las especies registradas y el 56% de los vertebrados amenazados, lo que sugiere un elevado valor de conservación. Las imágenes satelitales mostraron que el área del bosque natural en la zona fronteriza declinó en un 5.2% (13,255 km2) entre 1995 y 2018 y que los sembradíos de monocultivos incrementaron en un 92.4%, los matorrales en un 10.1% y otras tierras de cultivo en un 6.2%. La declinación resultante en el bosque natural conectado redujo la cantidad del hábitat, especialmente para los especialistas del bosque con habilidades limitadas de dispersión. La declinación más grave en la conectividad ocurrió a lo largo de la frontera entre China y Vietnam. Muchas áreas prioritarias atraviesan las fronteras internacionales, lo que indica una demanda y un potencial para el establecimiento de áreas protegidas transfronterizas. Nuestros resultados ejemplifican la importancia de la cooperación bi‐ y multilateral para proteger la biodiversidad en esta región y proporciona información para la planeación y práctica de la conservación en el futuro. 中国及其毗邻缅甸、老挝和越南边境上的保护规划 跨境保护在维持生态系统完整和阻止人类活动引起的生物多样性丧失方面起着重要的作用。然而, 跨境区域的物种分布信息和所受威胁的认识都很匮乏, 这不利于进一步的保护。在印‐缅生物多样性热点地区, 我们为中国云南省及其毗邻的缅甸, 老挝和越南的跨境区域提供了一个空间保护计划。通过分析物种分布格局, 近期土地利用变化以及为大多数物种提供了生境的天然林的连通性时空动态, 我们识别了该跨境区域的保护和恢复优先区。我们利用等同连接面积(ECA)指数来评估连通性。该指数可以测量一个物种在其扩散距离范围内可以到达的总的生境数量。我们从标本和专著中收集了21,004个植物和脊椎动物物种并分析了197,845条分布记录, 结果显示云南省边境地区具有最高的物种丰富度, 61%的已记录的物种和56%的受威胁脊椎动物分布在云南边境地区, 这表明边境地区具有高的保护价值。卫星影像分析显示, 从1995至2018年, 跨境区域天然林面积减少了5.2% (13,255 km2), 而单一种植的人工林面积增加了92.4%, 灌丛面积增加了10.1%, 农田面积增加了6.2%。由此引起的连通的天然林面积的下降减少了生境数量, 这对扩散能力较弱的森林特化物种的影响尤为明显。中‐越边境上的连通性下降最为严重。许多优先区跨越了国界线, 这表明了建立跨境保护地的需求和潜力。我们的结果阐明了双边或多边合作保护生物多样性的重要性, 同时也为该跨境区域未来的保护规划和实践提供了指导。 Article impact statement: Species distribution pattern and connectivity change call for transboundary conservation on China's borders with Myanmar, Laos, and Vietnam.